IDF (intensity-duration-frequency) curve and unit hydrograph as signature of characteristic changing of Way Kuala Garuntang Watershed. Issue 1 (April 2021) - Jokowinarno, D; Banuwa, I S; Yuwono, S B; Tugiyono,; Bakri, S; Setiawan, A
Abstract: There is direct relation between global warming and precipitation. Air capacity of water increase by 7% to increasing of 1°C of air temperature, causing more water vapor content in the air. This research aims to investigate how IDF Curve and Unit Hydrograph can be used as signature of characteristic changing of Way Kuala Garuntang Watershed. The study area is Way Kuala Garuntang watershed and rainfall data source is from automatic rainfall recorder of Stasiun BMKG Maritim Panjang, ARR Tipping bucket installed at Way Kuala Garuntang watershed, and 4 manual raingauges. From the research can be concluded that IDF Curve can be used as signature of characteristic changing of Way Kuala Garuntang watershed mainly the changing of rainfall intensity in various of return period. Meanwhile, due to average of IUH of 5 flood events in 1 year data serie, and significant differences of Qp between IUH and SUH, the Unit Hydrograph was not suitable as signature of characteristic changing of Way Kuala Garuntang watershed.